Was Cain Angry or Depressed? - Gruber, Mayer Irwin 1944- (1980)
The first murder recounted in the Bible is Cain’s slaying of Abel (Genesis 4). Cain, the farmer, brought an unidentified agricultural offering to the Lord. Abel, the shepherd, on the other hand, brought the first born of his flock. The Lord ignored Cain’s offering but highly regarded Abel’s. Cain’s reaction, according to most English […]